Changes of corneal optical properties after UVB irradiation investigated spectrophotometrically - Cejka, C; Pláteník, J; Sirc, J; Ardan, T; Michálek, J; Brůnová, B; Čejková, J (Physiological research, 2010)
Ozone depletion leads to an increase in UV rays of solar radiation reaching the surface of the Earth which is harmful to biological systems. Of the eye, the cornea is directly open to increased amount of UV rays of which mainly UVB rays are capable to induce reactive oxygen species damaging the cells. Previous studies showed that the irradiation of the cornea with UVB rays leads to morphological as well as metabolic disturbances of the cornea. Also, corneal hydration and corneal light absorption are increased after UVB rays. These changes were observed after five days of repeated irradiation of the cornea with UVB rays. The aim of the present paper was to examine how early the changes of corneal hydration and light absorption occur after UVB irradiation. The rabbit corneas were irradiated with UVB rays for one, two, three or four days. Corneal light absorption was examined spectrophotometrically and corneal hydration measured by pachymeter (as corneal thickness). Results show that changes of corneal hydration and light absorption appear early after UVB irradiation and increase along with the number of irradiations. In conclusion, irradiation of the rabbit cornea with UVB rays leads to harmful changes of its optical properties.
Keywords: rohovka; světlo; experimentální radiační poranění; Spectrophotometry; absorpce; zvířata; ultrafialové záření; časové faktory; Light; Cornea; Body Water; Radiation Injuries, Experimental; tělesná voda; králíci; spektrofotometrie; Absorption; Animals; Ultraviolet Rays; Disease Models, Animal; Time Factors; Rabbits; modely nemocí na zvířatech